Electric storage element and method for manufacturing the same
By using graphite as the negative electrode active material and using a solvent-based adhesive to avoid pressure application, the problem of insufficient durability of the negative electrode material of lithium-ion batteries is solved, and the capacity maintenance rate and service life of the battery in a charged state is improved.
Patent Information
- Application Number
- JP2021558276
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-18
- Filing Date
- 2020-11-05
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-11-05
AI Technical Summary
The negative electrode material of existing lithium-ion batteries is insufficient in a charged state, resulting in low capacity maintenance.
Graphite is used as the negative electrode active material and a solvent-based adhesive is used to avoid applying pressure to the negative electrode active material layer, ensure uniformity of ion transport, and form the negative electrode active material layer by directly coating and drying on the negative electrode substrate.
The capacity maintenance rate of the negative electrode material in the charging state is improved, the occurrence of uneven reactions is reduced, and the service life of the battery is extended.
Smart Images

Figure 0007626072000002 
Figure 0007626072000003 
Figure 0007626072000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an energy storage element and a method for manufacturing an energy storage element. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion non-aqueous electrolyte secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally include an electrode assembly having a pair of electrodes electrically isolated by a separator, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as storage elements other than non-aqueous electrolyte secondary batteries.
[0003] Carbon materials such as graphite are used as the negative electrode active material of the electricity storage element (see Patent Document 1). 2 The invention relates to a negative electrode material for lithium batteries, which is characterized by containing a carbon-based negative electrode active material having a molecular weight of 1000 to 10000 μm / g or more, a binder made of styrene-butadiene rubber (SBR), and carbon fibers having a fiber diameter of 1 to 1000 nm. Patent Document 1 describes a method of producing a negative electrode material by applying a negative electrode material composition to a current collector foil, drying it, and then pressing it. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2005-222933 Summary of the Invention [Problem to be solved by the invention]
[0005] The durability of an electric storage element having a negative electrode containing a carbon material as a negative electrode active material and SBR, which is a water-based binder, as a binder, as described in the above Patent Document 1 is insufficient. Specifically, the inventors have confirmed that the electric storage element having the above configuration has a low capacity retention rate after being left in a charged state.
[0006] The present invention aims to provide an energy storage element that uses graphite as a negative electrode active material and has a high capacity retention rate after being left in a charged state, and a method for manufacturing such an energy storage element. [Means for solving the problem]
[0007] An energy storage element according to one embodiment of the present invention is an energy storage element comprising: a negative electrode substrate; a negative electrode having a negative electrode active material layer laminated on the negative electrode substrate directly or via another layer; and a non-aqueous electrolyte solution, wherein the negative electrode active material layer contains graphite and a solvent-based binder, and the negative electrode active material layer is not pressed.
[0008] According to another aspect of the present invention, there is provided an energy storage element comprising: a negative electrode substrate; a negative electrode having a negative electrode active material layer laminated on the negative electrode substrate directly or via another layer; and a non-aqueous electrolyte solution, wherein the negative electrode active material layer contains graphite and a solvent-based binder, and the ratio of the surface roughness of the negative electrode substrate in a region where the negative electrode active material layer is not laminated to the surface roughness of the negative electrode substrate in a region where the negative electrode active material layer is laminated is 0.90 or more.
[0009] A method for manufacturing an electric storage element according to another aspect of the present invention includes laminating a negative electrode active material layer directly or via another layer on a negative electrode base material, and preparing a non-aqueous electrolyte solution, wherein the negative electrode active material layer contains graphite and a solvent-based binder, and the method does not include pressing the negative electrode active material layer. Effect of the Invention
[0010] According to one aspect of the present invention, it is possible to provide an energy storage element that uses graphite as a negative electrode active material and has a high capacity retention rate after being left in a charged state, and a method for manufacturing such an energy storage element. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic exploded perspective view showing an energy storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an energy storage element according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic diagram showing an electricity storage device formed by assembling a plurality of electricity storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] First, an overview of the energy storage element and the method for manufacturing the energy storage element disclosed in this specification will be described.
[0013] An electric storage element according to one embodiment of the present invention is an electric storage element (A) including: an electric storage element (A) that includes: an electric storage element (A) including: an electric storage element (A) that includes: an electric storage element (A) including: an electric storage element (A) including: an electric storage element (A) including: an electric storage element (A) including: an electric storage element (A) including: an electric storage element (A) including: an electric storage element (A) including: an electric storage element (A) including: an electric storage element (A) including: an electric storage element (A) including: an electric storage element (A)
[0014] The storage element (A) is a storage element using graphite as a negative electrode active material, and has a high capacity retention rate after being left in a charged state. The reason for this is unclear, but is presumed to be as follows. Aqueous binders such as SBR have low swelling properties with respect to non-aqueous electrolyte, and the amount of non-aqueous electrolyte near the aqueous binder is less than that in other parts, which tends to become a resistance component during charging and discharging. For this reason, when an aqueous binder is used in the negative electrode active material layer, the vicinity of the aqueous binder in the negative electrode becomes highly resistive, and ion migration at the interface between the negative electrode active material and the non-aqueous electrolyte becomes non-uniform, which tends to cause reaction unevenness in the negative electrode. In a storage element in which reaction unevenness occurs in the negative electrode, when the storage element is left in a charged state, it is considered that the deterioration of the storage element material due to the reaction unevenness progresses, and the capacity after being left is likely to decrease. On the other hand, when a solvent-based binder having high swelling property with respect to a non-aqueous electrolyte is used in the negative electrode active material layer, the ion migration at the interface between the negative electrode active material and the non-aqueous electrolyte is maintained in a highly uniform state, and it is considered that the reaction unevenness of the negative electrode is suppressed, and the decrease in capacity after standing is also suppressed. In addition, the negative electrode expands due to the insertion of lithium ions into the graphite during initial charging, but when the negative electrode active material layer is pressed in the manufacturing process, the residual stress caused by the press is released, and therefore the expansion is particularly likely to be uneven. If the expansion of the negative electrode is uneven, the distance between the positive electrode and the negative electrode becomes uneven, which is also considered to be a factor in causing the reaction unevenness. Furthermore, when the negative electrode active material layer is pressed, the surface coat of the graphite may peel off, and the charge / discharge performance of the graphite itself may be reduced. On the other hand, when the negative electrode active material layer is not pressed, the above-mentioned reaction unevenness is also suppressed, and the decrease in the charge / discharge performance of the graphite is also suppressed. For these reasons, it is presumed that the storage element (A) in which the negative electrode active material layer contains graphite and a solvent-based binder and in which the negative electrode active material layer is not pressed can exhibit the effect of having a high capacity retention rate after being left in a charged state.
[0015] In addition, "graphite" refers to a material that has an average lattice spacing (d 002) is 0.33 nm or more and less than 0.34 nm. Here, the "discharged state" refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metal Li as a counter electrode. Since the potential of the metal Li counter electrode in the open circuit state is almost equal to the oxidation-reduction potential of Li, the open circuit voltage in the single-electrode battery is almost equal to the potential of the negative electrode containing the carbon material relative to the oxidation-reduction potential of Li. In other words, the open circuit voltage of the single-electrode battery being 0.7 V or more means that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material. In addition, the "solvent-based binder" refers to a binder that is dispersed or dissolved in an organic solvent.
[0016] "Not pressed" means that during production, a process of applying a pressure (linear pressure) of 10 kgf / mm or more to the negative electrode active material layer is not performed using a device designed to apply pressure to a workpiece, such as a roll press. In other words, "not pressed" also includes a process in which a slight pressure is applied to the negative electrode active material layer in other processes, such as winding the negative electrode. "Not pressed" also includes a process in which a pressure (linear pressure) of less than 10 kgf / mm is applied.
[0017] Another aspect of the present invention relates to an energy storage element (B) that includes: an anode substrate; an anode having an anode active material layer laminated on the anode substrate directly or via another layer; and a non-aqueous electrolyte; the anode active material layer contains graphite and a solvent-based binder; and a ratio (R2 / R1) of a surface roughness R2 of the anode substrate in a region where the anode active material layer is not laminated to a surface roughness R1 of the anode substrate in a region where the anode active material layer is laminated is 0.90 or more.
[0018] The storage element (B) is an electric storage element using graphite as the negative electrode active material, and has a high capacity retention rate after being left in a charged state. In a negative electrode in which a negative electrode active material layer is laminated on a negative electrode substrate, the stronger the negative electrode active material layer is pressed, the larger the surface roughness R1 of the region in the negative electrode substrate where the negative electrode active material layer is laminated, and therefore the ratio (R2 / R1) to the surface roughness R2 of the region in which the negative electrode active material layer is not laminated becomes smaller. In other words, when not pressed, the surface roughness is almost the same in the region in which the negative electrode active material layer is disposed and the region in which the negative electrode active material layer is not disposed (for example, in the case where the negative electrode substrate has a portion where the negative electrode substrate is exposed, the exposed region of the negative electrode substrate). That is, the ratio (R2 / R1) approaches 1. In the storage element (B), the ratio (R2 / R1) is 0.90 or more, which means that there is no or small pressure applied to the negative electrode active material layer in a state where it is laminated on the negative electrode substrate. In addition, the electric storage element (B) uses a solvent-based binder as the binder for the negative electrode active material layer, similarly to the electric storage element (A) described above. Therefore, it is presumed that the electric storage element (B) can exhibit the effect of having a high capacity retention rate after being left in a charged state for the same reason as the electric storage element (A) described above.
[0019] The "surface roughness" of the negative electrode substrate means the arithmetic mean roughness Ra of the surface of the negative electrode substrate (for the region where the negative electrode active material layer and other layers are laminated, the surface after removing these layers) measured with a laser microscope in accordance with JIS-B0601 (2013). Specifically, it can be a measured value by the following method. First, if the negative electrode has a portion where the negative electrode substrate is exposed, the surface roughness of this portion is taken as the surface roughness R2 of the region where the negative electrode active material layer is not disposed, and is measured in accordance with JIS-B0601 (2013) using a commercially available laser microscope (manufactured by Keyence Corporation, device name "VK-8510"). At this time, the measurement conditions are a measurement region (area) of 149 μm × 112 μm (16688 μm 2), the measurement pitch is 0.1 μm. Next, the negative electrode is shaken using an ultrasonic cleaner to remove the negative electrode active material layer and other layers from the negative electrode substrate. The surface roughness R1 of the region where the negative electrode active material layer was laminated is measured in the same manner as the surface roughness of the portion where the negative electrode substrate is exposed. In addition, when there is no portion where the negative electrode substrate is exposed on the negative electrode (for example, when the entire surface of the negative electrode substrate is covered with an intermediate layer described later), the surface roughness of the region where the negative electrode active material layer was not arranged (for example, the region covered with the intermediate layer and where the negative electrode active material layer was not arranged) is measured in the same manner as the surface roughness R2 of the region where the negative electrode active material layer is not arranged. Shaking using an ultrasonic cleaner can be performed by shaking the Branson tabletop ultrasonic cleaner "2510J-DTH" while immersing in water for 3 minutes and then in ethanol for 1 minute.
[0020] In the electric storage element (A) and the electric storage element (B), it is preferable that the graphite contains solid graphite. When the graphite contains solid graphite, the capacity retention rate after being left in a charged state tends to be higher. Although the reason for this is unclear, it is presumed that when the graphite is solid, the density in the graphite particles is uniform and current concentration is unlikely to occur, so that reaction unevenness in the negative electrode is further reduced. In addition, when the graphite contains solid graphite, non-uniform expansion of the negative electrode can be suppressed, and expansion during initial charging is also reduced.
[0021] Here, "solid" means that the inside of the particle is filled and there is substantially no void. Specifically, solid means that in a cross section of the particle observed in an SEM image obtained using a scanning electron microscope (SEM), the area ratio excluding voids in the particle to the area of the entire particle is 95% or more. In a preferred embodiment, the area ratio of the solid graphite particles may be 97% or more (e.g., 98% or more). The upper limit of the area ratio of the solid graphite particles may be 100%. The area ratio R can be determined as follows. (1) Preparation of the measurement sample The graphite particles to be measured are fixed in a thermosetting resin. A cross-section polisher is used to expose the cross-section of the graphite particles fixed in the resin, and the measurement sample is prepared. (2) Obtaining SEM (scanning electron microscope) images To obtain SEM images, a JSM-7001F (manufactured by JEOL Ltd.) scanning electron microscope is used. SEM images are obtained by observing secondary electron images. The acceleration voltage is 15 kV. The observation magnification is set so that 3 to 15 graphite particles appear in one field of view. The obtained SEM image is saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus are appropriately set so that the contours of the graphite particles are clearly visible. (3) Cutting out the outline of a graphite particle The image cutting function of the image editing software Adobe Photoshop Elements 11 is used to cut out the outlines of the graphite particles from the acquired SEM image. This cutting out of the outlines is performed by using the quick selection tool to select the area outside the outlines of the graphite particles, and then editing everything except the graphite particles to a black background. If the outlines of less than three graphite particles could be cut out at this time, another SEM image is acquired and the process is repeated until the outlines of three or more graphite particles can be cut out. (4) Binarization The image of the first graphite particle among the cut-out graphite particles is binarized using the image analysis software PopImaging 6.00, with a threshold value set to a concentration 20% lower than the concentration at which the intensity is at its maximum. The area of the lower concentration side is calculated by the binarization process to obtain the "area S1 excluding voids in the particle". Next, the image of the first graphite particle, the same as above, is binarized with a threshold value of concentration 10. The outer edge of the graphite particle is determined by the binarization process, and the area inside the outer edge is calculated to obtain the "area S0 of the entire particle". The ratio of S1 to S0 (S1 / S0) calculated above is used to calculate the "area ratio R1 (=S1 / S0) of the first graphite particle to the area of the entire particle excluding voids in the particle". The images of the second and subsequent graphite particles among the cut-out graphite particles are also binarized as described above to calculate the areas S1 and S0. Based on the calculated areas S1 and S0, the area ratios R2, R3, . . . of each graphite particle are calculated. (5) Determination of area ratio R The "area ratio R of graphite particles excluding voids within the particles to the total area of the particles" is determined by calculating the average value of all the area ratios R1, R2, R3, ... calculated by the binarization process.
[0022] In the electric storage element (A) and the electric storage element (B), the average particle size of the graphite is preferably 10 μm or less. In such a case, the capacity retention rate after being left in a charged state tends to be higher. Although the reason for this is unclear, it is presumed that when the average particle size of the graphite is small, the density of the negative electrode active material layer is made uniform and current concentration is unlikely to occur, thereby further reducing reaction unevenness in the negative electrode.
[0023] The term "average particle size" refers to the value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by the laser diffraction / scattering method for a diluted solution in which particles are diluted with a solvent in accordance with JIS-Z-8825 (2013). Specifically, the measured value can be measured using the following method. Measurements are performed using a laser diffraction particle size distribution analyzer (Shimadzu Corporation's "SALD-2200") as the measuring device and Wing SALD-2200 as the measurement control software. A scattering measurement mode is used, and a laser beam is irradiated onto a wet cell in which a dispersion liquid in which the measurement sample is dispersed in a dispersion solvent is circulated, and a scattered light distribution is obtained from the measurement sample. The scattered light distribution is then approximated by a log-normal distribution, and the particle size at which the cumulative degree is 50% is taken as the average particle size (D50).
[0024] A method for manufacturing an electric storage element according to another aspect of the present invention includes laminating a negative electrode active material layer directly or via another layer on a negative electrode base material, and preparing a non-aqueous electrolyte solution, wherein the negative electrode active material layer contains graphite and a solvent-based binder, and the method does not include pressing the negative electrode active material layer.
[0025] According to this manufacturing method, it is possible to manufacture an energy storage element that uses graphite as a negative electrode active material and has a high capacity retention rate after being left in a charged state.
[0026] Hereinafter, an energy storage device according to an embodiment of the present invention, a method for manufacturing an energy storage device, and other embodiments will be described in detail. Note that the names of the components (elementary components) used in each embodiment may differ from the names of the components (elementary components) used in the background art.
[0027] <Electricity storage element> An electric storage element according to one embodiment of the present invention includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode and the negative electrode are usually stacked or wound with a separator interposed therebetween to form an electrode body. This electrode body is housed in a case, and the case is filled with a non-aqueous electrolyte. The non-aqueous electrolyte is interposed between the positive electrode and the negative electrode. As an example of an electric storage element, a non-aqueous electrolyte secondary battery (hereinafter, also simply referred to as a "secondary battery") will be described.
[0028] [Positive electrode] The positive electrode has a positive electrode substrate and a positive electrode active material layer laminated on the positive electrode substrate directly or via an intermediate layer, which is another layer.
[0029] (Positive electrode substrate) The positive electrode substrate is a substrate having electrical conductivity. "Conductivity" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 "Non-conductive" means that the volume resistivity is 10 7 It means that the resistance is more than Ω·cm. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, etc. or alloys thereof are used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity, and cost. As the positive electrode substrate, foil, vapor deposition film, etc. can be mentioned, and foil is preferred from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085, A3003, etc. specified in JIS-H-4000 (2014).
[0030] The average thickness of the positive electrode substrate is preferably 3 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, even more preferably 8 μm or more and 30 μm or less, and particularly preferably 10 μm or more and 25 μm or less. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate while increasing the energy density per volume of the secondary battery. The "average thickness" refers to the value obtained by dividing the mass of a substrate of a given area by the true density and area of the substrate. The "average thickness" is also defined in the same way when used for a negative electrode substrate.
[0031] (Middle class) The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains conductive particles such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and includes, for example, a resin binder and conductive particles. The intermediate layer may cover a part of the positive electrode substrate, or may cover the entire surface.
[0032] (Cathode active material layer) The positive electrode active material layer contains a positive electrode active material and, as necessary, optional components such as a conductive agent, a binder, a thickener, and a filler.
[0033] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Co 1-x-γ ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Mn 1-x-γ ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co 1-x-γ-β ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al 1-x-γ-β]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn 2-γ O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species consisting of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used. In a preferred embodiment, the positive electrode active material may be a lithium nickel-containing composite oxide containing nickel as a transition metal. In a preferred embodiment, the positive electrode active material may be a lithium nickel cobalt manganese-containing composite oxide containing nickel, cobalt, and manganese as transition metals.
[0034] The positive electrode active material is usually a particle (powder). The average particle diameter of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle diameter of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle diameter of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. When a composite of the positive electrode active material and another material is used, the average particle diameter of the composite is taken as the average particle diameter of the positive electrode active material.
[0035] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.
[0036] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.
[0037] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphitized carbon, non-graphitized carbon, graphene-based carbon, and the like. Examples of non-graphitized carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.
[0038] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % or more and 10 mass % or less, and more preferably 3 mass % or more and 9 mass % or less. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.
[0039] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0040] The binder content in the positive electrode active material layer is preferably 1% by mass to 10% by mass, more preferably 2% by mass to 9% by mass (for example, 3% by mass to 6% by mass). By setting the binder content in the above range, the active material can be stably held.
[0041] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. When a thickener is used, the ratio of the thickener to the entire positive electrode active material layer can be about 8 mass % or less, and usually, it is preferably about 5.0 mass % or less (for example, 1.0 mass % or less). The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain the thickener.
[0042] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. When a filler is used, the proportion of the filler in the entire positive electrode active material layer can be about 8.0 mass% or less, and is usually about 5.0 mass% or less (for example, 1.0 mass% or less). The technology disclosed herein can be preferably implemented in an embodiment in which the positive electrode active material layer does not contain the filler.
[0043] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0044] [Negative electrode] The negative electrode has a negative electrode substrate and a negative electrode active material layer laminated on the negative electrode substrate directly or via an intermediate layer, which is another layer. The configuration of the intermediate layer is not particularly limited, and can be selected from the configurations exemplified for the positive electrode. The intermediate layer may cover a part of the negative electrode substrate, or may cover the entire surface. The negative electrode active material layer is usually disposed along at least one surface of the negative electrode substrate. The negative electrode substrate may have a region where the negative electrode active material layer is not laminated. The negative electrode substrate may have a region where the intermediate layer is laminated and where the negative electrode active material layer is not laminated.
[0045] (Negative electrode substrate) The negative electrode substrate is a substrate having electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel or alloys thereof are used as the material of the negative electrode substrate, and copper or a copper alloy is preferred. The form of the negative electrode substrate may be a foil, a vapor deposition film, or the like, and foil is preferred from the viewpoint of cost. That is, copper foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0046] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the secondary battery.
[0047] (Negative electrode active material layer) The negative electrode active material layer contains graphite and a solvent-based binder. The graphite functions as a negative electrode active material. The negative electrode active material layer contains optional components such as other negative electrode active materials, conductive agents, thickeners, and fillers as necessary. The optional components such as conductive agents, thickeners, and fillers can be selected from the materials exemplified for the positive electrode above.
[0048] When a conductive agent is used in the negative electrode active material layer, the proportion of the conductive agent in the entire negative electrode active material layer can be about 10 mass % or less, and usually, it is preferably about 8.0 mass % or less (for example, 3.0 mass % or less). The technology disclosed here can be preferably implemented in an embodiment in which the negative electrode active material layer does not contain the conductive agent. When a thickener is used in the negative electrode active material layer, the proportion of the thickener in the entire negative electrode active material layer can be about 8 mass % or less, and usually, it is preferably about 5.0 mass % or less (for example, 1.0 mass % or less). The technology disclosed here can be preferably implemented in an embodiment in which the negative electrode active material layer does not contain the thickener. When a filler is used in the negative electrode active material layer, the proportion of the filler in the entire negative electrode active material layer can be about 8.0 mass % or less, and usually, it is preferably about 5.0 mass % or less (for example, 1.0 mass % or less). The technology disclosed here can be preferably implemented in an embodiment in which the negative electrode active material layer does not contain the filler.
[0049] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, solvent-based binder, thickener, and filler.
[0050] The graphite contained in the negative electrode active material layer can be appropriately selected from various known graphites. Examples of such known graphite include artificial graphite and natural graphite. Here, artificial graphite is a general term for graphite that is artificially produced. Natural graphite is a general term for graphite extracted from natural minerals. Specific examples of natural graphite include flake graphite (flake graphite), lump graphite, and earthy graphite. The graphite may be flat flake-like natural graphite, or spheroidized natural graphite obtained by spheroidizing the flake-like natural graphite. In a preferred embodiment, the graphite is artificial graphite. By using artificial graphite, the above-mentioned effects can be better exhibited. The graphite used in the negative electrode active material layer may be graphite with a coating (for example, an amorphous carbon coating) on the surface.
[0051] The graphite contained in the negative electrode active material layer is usually particulate. The graphite may be either solid graphite or hollow graphite. However, the graphite preferably contains solid graphite, since it can further increase the capacity retention rate after being left in a charged state and can further suppress the expansion of the negative electrode during initial charging. The content of solid graphite in the graphite is preferably 20% by mass or more, more preferably 50% by mass or more, even more preferably 70% by mass or more, even more preferably 90% by mass or more, and particularly preferably substantially 100% by mass. Note that hollow graphite means graphite having voids inside the particles, and the above-mentioned area ratio R is less than 95%. In a preferred embodiment, the area ratio of the hollow graphite particles may be 92% or less (e.g., 90% or less). The lower limit of the area ratio of the hollow graphite particles may be, for example, 60%, 70%, or 80%.
[0052] The above average lattice spacing of graphite (d 002 ) is 0.33 nm or more and less than 0.34 nm, and preferably 0.335 nm or more and less than 0.338 nm.
[0053] The shape of the graphite particles is preferably close to a perfect sphere, but may be spindle-shaped, flaky, plate-shaped, etc., and may have an uneven surface. The graphite particles may include particles in which a plurality of graphite particles are aggregated. The electric storage device disclosed herein may be preferably implemented in an embodiment that does not substantially include flaky graphite particles. This allows the negative electrode active material layer to have a high packing density despite being non-pressed. Such an electric storage device can effectively increase the battery capacity (energy density) per volume, and can also increase the capacity retention rate after being left in a charged state.
[0054] The negative electrode active material layer disclosed herein may contain multiple types of graphite particles, or may contain only one type of graphite particles. When the negative electrode active material layer contains multiple types of graphite particles, the number of types of graphite particles contained in the negative electrode active material layer can usually be roughly understood based on the difference in the external shapes of the multiple types of graphite particles. The difference in the external shapes of the graphite particles can be at least one of, for example, a difference in average particle size, a difference in average aspect ratio, a difference in the surface shape of the particles (for example, the presence or absence and the degree of surface unevenness, the presence or absence and the degree of surface coating), and a difference in the internal density of the particles. The external shape of the graphite particles can be understood, for example, from an SEM image. The negative electrode active material layer disclosed herein can be preferably implemented in an embodiment containing only one type of graphite particles. This makes it possible to more suitably exhibit the above-mentioned effects while making the most of the advantages of using the one type of graphite particles.
[0055] The aspect ratio of the graphite particles is preferably 1.0 to 5.0, more preferably 2.0 to 4.0. By setting the aspect ratio of the graphite particles within the above range, the graphite particles become closer to a sphere, and current concentration is less likely to occur, so that uneven expansion of the negative electrode and a decrease in the capacity retention rate after being left in a charged state can be more suppressed. In addition, the negative electrode active material layer can be made to have a high packing density without pressing the negative electrode active material layer. In such a storage element, the battery capacity (energy density) per volume can be effectively increased, and the capacity retention rate after being left in a charged state can be increased.
[0056] The "aspect ratio" refers to the A / B value, which is the ratio of the longest diameter A of a particle to the longest diameter B in the direction perpendicular to diameter A, in the cross section of the particle observed in an SEM image obtained using a scanning electron microscope. The aspect ratio can be determined as follows. (1) Preparation of the measurement sample A measurement sample is used in which the cross section used in determining the above-mentioned area ratio R is exposed. (2) Acquiring SEM images To obtain SEM images, a JSM-7001F (manufactured by JEOL Ltd.) scanning electron microscope is used. The conditions for obtaining SEM images are for observing secondary electron images. The acceleration voltage is 15 kV. The observation magnification is set so that 100 to 1000 graphite particles appear in one field of view. The obtained SEM image is saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus are appropriately set so that the contours of the graphite particles are clearly visible. (3) Determining the aspect ratio From the acquired SEM image, 100 graphite particles are randomly selected, and for each, the longest diameter A of the graphite particle and the longest diameter B in the direction perpendicular to diameter A are measured, and the A / B value is calculated. The aspect ratio of the graphite particle is determined by calculating the average value of all the calculated A / B values.
[0057] The average particle size of graphite (graphite particles) may be, for example, 0.1 μm or more and 30 μm or less (typically 0.3 μm or more and 25 μm or less), but is preferably 0.5 μm or more and 15 μm or less, more preferably 1 μm or more and 10 μm or less, and even more preferably 1.5 μm or more and 5 μm or less. In some embodiments, the average particle size of graphite may be, for example, 4 μm or less, typically 3 μm or less. By setting the average particle size of graphite to the above upper limit or less, the capacity retention rate after being left in a charged state can be further increased. In addition, by setting the average particle size of graphite to the above lower limit or more, the ease of handling during production can be improved.
[0058] The true density of the graphite particles is 2.1 g / cm3 The use of graphite particles with such a high true density makes it possible to increase the energy density. On the other hand, the upper limit of the true density of the graphite particles is, for example, 2.5 g / cm. 3 The true density is measured by the gas volumetric method using a pycnometer with helium gas.
[0059] The content of graphite in all negative electrode active materials is preferably 50% by mass or more, more preferably 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more. The content of graphite may be 100% by mass, more preferably 98% by mass or less or 95% by mass or less. The content of solid graphite in all negative electrode active materials is preferably 50% by mass or more, more preferably 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more. The content of hollow graphite may be 100% by mass, more preferably 98% by mass or less or 95% by mass or less. By making the content of graphite or solid graphite to be the above lower limit or more, it is possible to increase the capacity retention rate after being left in a charged state, the charge and discharge efficiency, etc.
[0060] The graphite content in the negative electrode active material layer is preferably 60% by mass or more and 99% by mass or less, and more preferably 90% by mass or more and 98% by mass or less. By setting the graphite content in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.
[0061] In some cases, it may be preferable for the negative electrode active material layer to contain non-graphitic carbon together with graphite as the negative electrode active material. "Non-graphitic carbon" refers to a material having an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitic carbon include non-graphitizable carbon and graphitizable carbon, and non-graphitizable carbon is preferable. Examples of non-graphitic carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.
[0062] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.
[0063] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.
[0064] The average particle size of the non-graphitic carbon may be, for example, from 1 μm to 10 μm, and is preferably from 2 μm to 5 μm from the viewpoint of improving the filling property of the negative electrode active material in the negative electrode.
[0065] The content of non-graphitic carbon in the total negative electrode active material may be preferably 5% by mass to 40% by mass, more preferably 10% by mass to 30% by mass. By setting the content of non-graphitic carbon within the above range, the porosity of the negative electrode can be reduced, and an energy storage element having a negative electrode with a high packing density of the active material can be obtained.
[0066] The negative electrode active material layer may further contain other negative electrode active materials other than graphite and non-graphitic carbon. Examples of other negative electrode active materials include metals such as Si and Sn, oxides of these metals, and composites of these metals and carbon materials. However, the content of carbon materials such as graphite and non-graphitic carbon in all negative electrode active materials is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably substantially 100 mass% in some cases.
[0067] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 90% by mass to 98% by mass. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.
[0068] The solvent-based binder is not particularly limited as long as it is a binder that disperses or dissolves in an organic solvent. For example, the solvent-based binder is preferably one that dissolves in less than 1 part by mass in 100 parts by mass of water at 20°C. Examples of binders that disperse or dissolve in an organic solvent include fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), copolymers of vinylidene fluoride and hexafluoropropylene, etc.), polyethylene, polypropylene, polyimide, copolymers of ethylene and vinyl alcohol, polyacrylonitrile, polyphosphazene, polysiloxane, polyvinyl acetate, polymethyl methacrylate, polystyrene, polycarbonate, polyamide, polyamideimide, crosslinked polymers of cellulose and chitosan pyrrolidone carboxylate, chitin or chitosan derivatives, etc., and fluororesins are preferred, and PVDF is more preferred. One or more types of solvent-based binders can be used.
[0069] The content of the solvent-based binder in the negative electrode active material layer is preferably 0.5% by mass or more and 10% by mass or less, more preferably 1% by mass or more and 5% by mass or less. In a storage element having a negative electrode active material layer with a content of the solvent-based binder in the above range, the application effect of this embodiment can be more suitably exhibited. In addition, the active material can be stably held.
[0070] In one embodiment of the present invention, the negative electrode active material layer is disposed on the negative electrode substrate directly or through another layer without being pressed. In another embodiment of the present invention, the ratio (R2 / R1) of the surface roughness R2 of the negative electrode substrate in the region where the negative electrode active material layer is not laminated to the surface roughness R1 of the negative electrode substrate in the region where the negative electrode active material layer is laminated is 0.90 or more. The lower limit of the ratio (R2 / R1) is preferably 0.92, more preferably 0.94. On the other hand, the upper limit of the ratio (R2 / R1) is preferably 1.10, more preferably 1.05. In this way, by not pressing the negative electrode active material layer or by using a solvent-based binder in the negative electrode active material layer, the capacity retention rate after being left in a charged state can be increased, and the expansion of the negative electrode during initial charging can be suppressed.
[0071] The surface roughness R2 of the negative electrode substrate in a region where no negative electrode active material layer is laminated is, for example, 0.1 μm to 10 μm, and may be 0.3 μm to 3 μm.
[0072] The density of the negative electrode active material layer is not particularly limited, but for example, the lower limit is 0.8 g / cm 3 is preferred, and 1.0 g / cm 3 More preferably, 1.2 g / cm 3 More preferably, 1.4 g / cm 3 is even more preferable. By setting the density of the negative electrode active material layer to the above lower limit or more, it is possible to increase the energy density per volume. In addition, when solid graphite having a relatively small particle size is used as graphite, the negative electrode active material layer can have a high density without pressing the negative electrode active material layer, so that the energy density per volume can be increased while the capacity retention rate after being left in a charged state can be increased. On the other hand, the upper limit of the density of the negative electrode active material layer is, for example, 1.8 g / cm. 3 is preferred, and 1.6 g / cm 3 (For example, 1.55 g / cm 3 ) is more preferable, and 1.5 g / cm 3 is more preferred.
[0073] The density of the negative electrode active material layer is the mass per unit area of the negative electrode active material layer (g / cm 2 ) divided by the average thickness (cm). The average thickness of the negative electrode active material layer is the average value of thicknesses measured at five positions on ten negative electrodes cut into 2 cm x 1 cm pieces. The thickness of the negative electrode active material layer can be measured using a high-precision digimatic micrometer manufactured by Mitutoyo Corporation.
[0074] The average thickness of the negative electrode active material layer (when the negative electrode active material layer is formed on both sides of the negative electrode substrate, the total thickness of both sides, typically the average thickness at full charge) is not particularly limited, but for example, the lower limit is preferably 50 μm, more preferably 60 μm, even more preferably 70 μm, and even more preferably 80 μm. In some embodiments, the lower limit of the average thickness of the negative electrode active material layer may be, for example, 85 μm, typically 90 μm (e.g., 95 μm). On the other hand, the upper limit of the average thickness of the negative electrode active material layer is, for example, preferably 300 μm, more preferably 250 μm, and even more preferably 200 μm. In some embodiments, the upper limit of the average thickness of the negative electrode active material layer may be, for example, 180 μm, typically 150 μm (e.g., 120 μm). In a storage element having a negative electrode active material layer having the above average thickness, the application effect of this embodiment can be more suitably exhibited.
[0075] The porosity of the negative electrode active material layer is not particularly limited, but the upper limit is, for example, preferably 60%, more preferably 55%. In some embodiments, the porosity of the negative electrode active material layer may be, for example, 45% or less, typically 35% or less (for example, 32% or less). On the other hand, the lower limit of the porosity of the negative electrode active material layer is, for example, preferably 20%, more preferably 22%. In some embodiments, the porosity of the negative electrode active material layer may be, for example, 24% or more, typically 25% or more. When the porosity of the negative electrode active material layer is within such a range, a storage element with a high battery capacity (energy density) per volume can be realized. In this specification, the porosity of the negative electrode active material layer is calculated by the formula (1-V2 / V1)×100, where V1 is the apparent volume (volume including voids) of the negative electrode active material layer and V2 is the sum of the actual volumes of the materials constituting the negative electrode active material layer. The sum V2 of the actual volumes of the materials constituting the negative electrode active material layer can be calculated from the content of each material in the negative electrode active material layer and the true density of each material.
[0076] [Separator] The separator may be in the form of, for example, a woven fabric, a nonwoven fabric, or a porous resin film. Among these, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of the retention of a nonaqueous electrolyte. As the main component of the separator, a polyolefin such as polyethylene or polypropylene is preferred from the viewpoint of strength, and a polyimide or aramid is preferred from the viewpoint of resistance to oxidation and decomposition. These resins may also be combined.
[0077] An inorganic layer may be disposed between the separator and the electrode (usually, the positive electrode). This inorganic layer is a porous layer also called a heat-resistant layer. A separator having an inorganic layer formed on one or both sides of a porous resin film may also be used. The inorganic layer is usually composed of inorganic particles and a binder, and may contain other components.
[0078] [Nonaqueous electrolyte] The nonaqueous electrolyte may be a known nonaqueous electrolyte that is generally used in a general nonaqueous electrolyte secondary battery (electric storage element). The nonaqueous electrolyte generally contains a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.
[0079] As the non-aqueous solvent, a known non-aqueous solvent that is generally used as a non-aqueous solvent for a general non-aqueous electrolyte for a storage element can be used. As the non-aqueous solvent, cyclic carbonate, chain carbonate, ester, ether, amide, sulfone, lactone, nitrile, etc. can be mentioned. Among these, it is preferable to use at least one of cyclic carbonate and chain carbonate, and it is more preferable to use cyclic carbonate and chain carbonate in combination. When using cyclic carbonate and chain carbonate in combination, the volume ratio of cyclic carbonate to chain carbonate (cyclic carbonate: chain carbonate) is not particularly limited, but is preferably, for example, 5:95 to 50:50.
[0080] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate, with EC being preferred.
[0081] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diphenyl carbonate, and among these, EMC is preferred.
[0082] The electrolyte salt may be any known electrolyte salt commonly used in non-aqueous electrolyte solutions for general storage elements, such as lithium salt, sodium salt, potassium salt, magnesium salt, onium salt, etc., with lithium salt being preferred.
[0083] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a hydrocarbon group in which hydrogen is replaced by fluorine, such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0084] The lower limit of the content of the electrolyte salt in the nonaqueous electrolyte is 0.1 mol / dm 3 is preferred, and 0.3 mol / dm 3 More preferably, 0.5 mol / dm 3 More preferably, 0.7 mol / dm 3 On the other hand, the upper limit is not particularly limited, but is preferably 2.5 mol / dm 3 is preferred, and 2 mol / dm 3 More preferably, 1.5 mol / dm 3 is more preferred.
[0085] The non-aqueous electrolyte may contain an additive. Examples of the additive include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexyl benzene, and cyclohexyl benzene. hexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These additives may be used alone or in combination of two or more.
[0086] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.
[0087] [Specific configuration of the energy storage element] Next, a specific configuration example of an energy storage element according to one embodiment of the present invention will be described. FIG. 1 is a schematic exploded perspective view showing an electrode body and a case of an energy storage element according to one embodiment of the present invention. FIG. 2 is a schematic cross-sectional view of the energy storage element in FIG. 1. The energy storage element 1 includes an electrode body 2, a positive electrode current collector 4' and a negative electrode current collector 5' connected to both ends of the electrode body 2, and a case 3 for housing them. The energy storage element 1 includes the electrode body 2 housed in the case 3, and a non-aqueous electrolyte is disposed in the case 3. The electrode body 2 is formed by winding a positive electrode having a positive electrode active material and a negative electrode having a negative electrode active material in a flat shape with a separator interposed therebetween. In this embodiment, the winding axis direction of the electrode body 2 is the Z-axis direction, and the long axis direction in a cross section of the electrode body 2 perpendicular to the Z-axis is the X-axis direction. The direction perpendicular to the Z-axis and the X-axis is the Y-axis direction.
[0088] At one end of the positive electrode, there is an exposed region of the positive electrode substrate on which the positive electrode active material layer is not laminated. At one end of the negative electrode, there is an exposed region of the negative electrode substrate on which the negative electrode active material layer is not laminated. A positive electrode current collector 4' is electrically connected to the exposed region of the positive electrode substrate by clamping with a clip, welding, or the like, and a negative electrode current collector 5' is similarly electrically connected to the exposed region of the negative electrode substrate. The positive electrode is electrically connected to the positive electrode terminal 4 via the positive electrode current collector 4', and the negative electrode is electrically connected to the negative electrode terminal 5 via the negative electrode current collector 5'.
[0089] The case 3 is a rectangular parallelepiped housing that houses the electrode assembly 2, the positive electrode current collector 4', and the negative electrode current collector 5', and has one surface (top surface) perpendicular to the second direction (X direction) open. Specifically, the case 3 has a bottom surface, a pair of long side surfaces facing the third direction (Y direction), and a pair of short side surfaces facing the first direction (Z direction). The inner surface of the case 3 is in direct contact with the outer surface of the electrode assembly 2 (usually a separator). The case 3 may be provided with a spacer, sheet, etc. interposed between the case 3 and the electrode assembly 2. The material of the spacer, sheet, etc. is not particularly limited as long as it has insulating properties. When the case 3 is provided with a spacer, sheet, etc., the inner surface of the case 3 is indirectly in contact with the outer surface of the electrode assembly 2 via the spacer, sheet, etc.
[0090] The upper surface of the case 3 is closed by a lid 6. The case 3 and the lid 6 are made of a metal plate, a resin plate, etc. The metal plate can be made of aluminum, for example.
[0091] The lid 6 is provided with a positive electrode terminal 4 and a negative electrode terminal 5 that are electrically connected to the outside. The positive electrode terminal 4 is connected to a positive electrode current collector 4', and the negative electrode terminal 5 is connected to a negative electrode current collector 5'. Furthermore, a nonaqueous electrolyte is usually injected into the case 3 through an injection hole (not shown) provided in the lid 6.
[0092] The electrode assembly 2 has a positive electrode, a negative electrode, and a separator that insulates them, and the positive electrodes and negative electrodes are alternately stacked with the separator interposed between them. The electrode assembly 2 is a wound type electrode assembly in which a sheet body including a positive electrode, a negative electrode, and a separator is wound into a flat shape.
[0093] The electrode body 2 preferably has a hollow region in the central portion 8. In addition, when the electrode body 2 is configured by winding the positive electrode and the negative electrode on a winding core with a separator therebetween, it is preferable that the internal structure of the winding core is a hollow structure, or that the electrode body has a hollow region in the central portion 8 by having a partial gap without being in close contact with the outer surface of the winding core. In a wound electrode body in which the positive electrode and the negative electrode are wound in a stacked state, if there is a hollow portion where the electrode plate (positive electrode or negative electrode) or separator that is the innermost periphery of the electrode body does not exist, when the negative electrode expands, a part of the negative electrode may move into the hollow portion. In particular, since the negative electrode near the inner periphery is close to the hollow portion, it may move toward the hollow portion, resulting in a portion where the interelectrode distance between the positive electrode and the negative electrode becomes large. Such behavior of the inner periphery side of the wound electrode body is likely to occur when the outer periphery surface of the electrode body is in contact with the inner surface of the case, because the electrode body is difficult to move toward the outer periphery surface. In this way, when a portion where the interelectrode distance between the positive electrode and the negative electrode is large occurs, the resistance of the portion where the interelectrode distance is large increases, making it difficult for the charge / discharge reaction to occur, and the charge / discharge reaction is concentrated in the vicinity of the portion where the interelectrode distance is large. It is expected that such concentration of the charge / discharge reaction will cause charge / discharge unevenness near the inner circumference. Since the electrode body 2 has a hollow region in the central portion 8, peeling of the active material layer due to bending of the positive electrode or negative electrode located near the central portion 8 can be suppressed, and the energy storage element 1 has a high suppression effect against the expansion of the negative electrode that occurs during initial charging, so that charge / discharge unevenness due to the increase in the interelectrode distance that occurred in the conventional electrode body having a hollow region can be suppressed.
[0094] The material of the core is not particularly limited as long as it has insulating properties and is stable in the electrolyte, and examples of the material of the core include polyethylene and polypropylene.
[0095] [Pressure-sensitive electrical connection / disconnection mechanism and pressure-sensitive electrical short-circuit mechanism] The electric storage element according to one embodiment of the present invention is preferably provided with a pressure-sensitive cutoff mechanism that cuts off the electrical connection between the positive electrode and the negative electrode when the internal pressure rises to a predetermined pressure (preferably, a pressure of 0.2 MPa or more and 1.0 MPa or less), or a pressure-sensitive short-circuit mechanism that electrically shorts the positive electrode and the negative electrode outside the electrode body. When the electric storage element is overcharged or the nonaqueous electrolyte is decomposed, the internal pressure or temperature may increase significantly to such an extent that the charge / discharge performance required for the electric storage element cannot be exhibited. For this reason, in the conventional electric storage element, when the internal pressure rises due to overcharging or the like, a mechanism is provided to cut off the electrical connection between the positive electrode and the negative electrode or to electrically short the positive electrode and the negative electrode outside the electrode body by, for example, inverting the diaphragm, thereby further improving safety. However, in these mechanisms, if the expansion amount of the electrode plate increases, the internal pressure of the electric storage element increases, and the above mechanism may be activated early. The energy storage element of one embodiment of the present invention is provided with a mechanism for cutting off the electrical connection between the positive electrode and the negative electrode, or a mechanism for electrically shorting the positive electrode and the negative electrode outside the electrode body, thereby further improving safety, and since the energy storage element has a high suppressing effect against expansion of the negative electrode that occurs during initial charging, it is possible to suppress premature activation of the above-mentioned mechanism.
[0096] These mechanisms work by adding a compound to the non-aqueous electrolyte that promotes gas generation when the temperature or voltage increases, and by increasing the internal pressure of the storage element when an event such as overcharging occurs.
[0097] The pressure-sensitive electrical disconnection mechanism is provided, for example, in the conductive path between the positive electrode and the positive electrode terminal, or the conductive path between the negative electrode and the negative electrode terminal. When the pressure-sensitive electrical disconnection mechanism is activated, no charging current flows, so that the increase in the voltage of the storage element can be suppressed, and safety during overcharging is further improved. In the case of the pressure-sensitive electrical disconnection mechanism, when the internal pressure of the storage element increases due to, for example, overcharging of the storage element, the center part of the diaphragm rises, breaking the conductive path and cutting off the current. This prevents further charging when the storage element is overcharged.
[0098] The pressure-sensitive electrical short-circuit mechanism is provided, for example, outside the electrode body (for example, the negative electrode current collector 5' in FIG. 1). When the energy storage element is overcharged and the pressure inside the energy storage element exceeds a predetermined value, the pressure-sensitive electrical short-circuit mechanism causes the center portion of the metal diaphragm to rise, and the diaphragm comes into contact with the conductive member, resulting in a short circuit between the positive electrode and the negative electrode. This makes it possible to prevent a charging current from flowing into the electrode body. Since this short circuit occurs outside the electrode body, it is possible to suppress a temperature rise in the energy storage element due to an exothermic reaction in the active material layer, which would occur if a short circuit occurred inside the electrode body. In this way, safety is further improved when the energy storage element is overcharged.
[0099] [Pressure member] The electric storage element according to one embodiment of the present invention preferably includes a pressure member that applies pressure to the case from the outside. Since the electric storage element has a high suppression effect against the expansion of the negative electrode that occurs during initial charging, the frictional force between the case and the inner surface of the case due to the expansion of the electrode body is reduced, and it is possible that the electrode body may move within the case. By including a pressure member that applies pressure to the case from the outside, the electric storage element can increase the frictional force between the case and the electrode body, thereby improving the holding ability of the electrode body.
[0100] Examples of the pressure member include a restraining band attached to the outer periphery of the case, a metal frame, and the like.
[0101] <Method of manufacturing the energy storage element> A method for producing an electric storage element according to one embodiment of the present invention includes laminating a negative electrode active material layer directly or via another layer on a negative electrode substrate, and preparing a non-aqueous electrolyte solution.
[0102] In the process of laminating the negative electrode active material layer directly or via another layer on the negative electrode substrate, the negative electrode active material layer can be arranged along at least one surface of the negative electrode substrate by coating the negative electrode mixture on the negative electrode substrate. Specifically, for example, the negative electrode active material layer is laminated by coating the negative electrode mixture on the negative electrode substrate and drying it. As described above, the negative electrode active material layer contains graphite and a solvent-based binder. That is, the negative electrode mixture contains graphite and a solvent-based binder.
[0103] The negative electrode mixture may be a negative electrode mixture paste containing a dispersion medium in addition to the graphite, the solvent-based binder, and the optional components described above. The dispersion medium may be an organic solvent such as N-methylpyrrolidone (NMP) or toluene.
[0104] A negative electrode is produced through a step of laminating a negative electrode active material layer directly or via another layer on a negative electrode substrate. Note that this production method does not include pressing the negative electrode active material layer. The production method of an electric storage element according to one embodiment of the present invention may include a step of preparing a negative electrode having an unpressed negative electrode active material layer.
[0105] In the step of preparing the nonaqueous electrolyte, for example, the components constituting the nonaqueous electrolyte, such as an electrolyte salt and a nonaqueous solvent, are mixed together to prepare the nonaqueous electrolyte.
[0106] The manufacturing method may further include preparing a positive electrode, stacking the positive electrode and the negative electrode with a separator interposed therebetween to obtain an electrode body, housing the electrode body in a case, and injecting a nonaqueous electrolyte into the case.
[0107] In the step of preparing the positive electrode, a positive electrode active material layer containing a positive electrode active material can be arranged along at least one surface of the positive electrode substrate by coating the positive electrode mixture on the positive electrode substrate. Specifically, the positive electrode active material layer is laminated by coating the positive electrode mixture on the positive electrode substrate and drying it. The positive electrode mixture may be a positive electrode mixture paste containing a dispersion medium. The dispersion medium may be water or the like in addition to the organic solvent exemplified for the negative electrode mixture. The positive electrode may be pressed using a roll press or the like.
[0108] In addition to the above steps, the method may further include a step of housing the electrode body in a case and injecting a non-aqueous electrolyte into the case. The electrode body may be housed in the case after the non-aqueous electrolyte is injected into the case. The injection port is then sealed to obtain an energy storage element. Details of each element constituting the energy storage element obtained by the manufacturing method are as described above.
[0109] [Other embodiments] The electric storage element of the present invention is not limited to the above embodiment. In the above embodiment, the electric storage element is mainly a non-aqueous electrolyte secondary battery, but other electric storage elements may be used. Examples of other electric storage elements include a capacitor (electric double layer capacitor, lithium ion capacitor), etc.
[0110] In addition, while the above embodiment has been described focusing on a configuration using a wound electrode body, a laminated electrode body formed of a laminate of a plurality of sheets each including a positive electrode, a negative electrode, and a separator may also be provided.
[0111] The present invention can also be realized as an electricity storage device including a plurality of the above-mentioned electricity storage elements. Moreover, an electricity storage unit can be configured by using one or a plurality of the electricity storage elements (cells) of the present invention, and further, an electricity storage device can be configured by using this electricity storage unit. In this case, the technology of the present invention may be applied to at least one electricity storage element included in the electricity storage unit or the electricity storage device. The electricity storage device can be used as a power source for automobiles such as electric vehicles (EV), hybrid vehicles (HEV), plug-in hybrid vehicles (PHEV), and the like. Furthermore, the electricity storage device can be used in various power supply devices such as engine starting power supply devices, auxiliary power supply devices, and uninterruptible power supplies (UPS).
[0112] 3 shows an example of an energy storage device 30 in which energy storage units 20, each of which is an assembly of two or more electrically connected energy storage elements 1, are further assembled. The energy storage device 30 may include a bus bar (not shown) that electrically connects the two or more energy storage elements 1, and a bus bar (not shown) that electrically connects the two or more energy storage units 20. The energy storage units 20 or the energy storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more energy storage elements. EXAMPLES
[0113] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0114] [Example 1] (Preparation of negative electrode) A negative electrode mixture paste was prepared containing graphite A (solid graphite, average particle size 3 μm) as a negative electrode active material and PVDF (solvent-based binder) as a binder, with NMP as a dispersion medium. The ratio of the negative electrode active material to the binder was 95:5 by mass ratio. The negative electrode mixture paste was applied to both sides of a copper foil substrate (surface roughness Ra 0.74 μm) and dried to form a negative electrode active material layer, thereby obtaining the negative electrode of Example 1. The negative electrode active material layer was not pressed. For the obtained negative electrode, the area ratio R of graphite excluding voids within the particles, the average thickness of the negative electrode active material layer before charge / discharge, the density of the negative electrode active material layer, the porosity of the negative electrode active material layer, and the surface roughness ratio (R2 / R1) of the negative electrode base material were measured using the methods described above.
[0115] (Preparation of positive electrode) LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode mixture paste was prepared containing O2, PVDF as a binder, and acetylene black as a conductive agent, and NMP as a dispersion medium. The ratio of the positive electrode active material, the binder, and the conductive agent was 94:3:3 by mass ratio. The positive electrode mixture paste was applied to both sides of an aluminum foil substrate and dried. Then, the substrate was pressed to form a positive electrode active material layer, and a positive electrode was obtained.
[0116] (Preparation of non-aqueous electrolyte) A non-aqueous solvent consisting of a mixture of EC, EMC, and DMC in a volume ratio of 30:35:35 was added with 1.2 mol / dm LiPF as an electrolyte salt. 3 A non-aqueous electrolyte solution was prepared by mixing the above components so as to obtain a content of 1:1.
[0117] (Assembly of energy storage elements) The positive electrode and the negative electrode were laminated with a polyethylene separator having a thickness of 20 μm and wound to prepare a wound electrode body. The wound electrode body was prepared by placing a polypropylene resin sheet having a thickness of 0.3 mm at the center, the polypropylene resin sheet being rolled into a track shape and welded to form a core. The wound electrode body was housed in a case. At this time, the outer peripheral surface of the wound electrode body was in contact with the inner surface of the case via an insulating sheet. Next, the nonaqueous electrolyte was injected into the case to obtain the storage element of Example 1.
[0118] [Examples 2 to 3, Comparative Examples 1 to 6] In the preparation of the negative electrode, the negative electrodes of Examples 2 to 3 and Comparative Examples 1 to 6 were prepared in the same manner as in Example 1, except that the negative electrode active materials and binders shown in Table 1 were used and the negative electrode active material layer was pressed or not as shown in Table 1. In addition, the energy storage elements of Examples 2 to 3 and Comparative Examples 1 to 6 were obtained in the same manner as in Example 1, except that the negative electrodes of Examples 2 to 3 and Comparative Examples 1 to 6 were used.
[0119] In each comparative example in which the binder was styrene butadiene rubber (SBR), a negative electrode mixture paste was prepared containing the negative electrode active material, SBR as a binder, and carboxymethyl cellulose (CMC) as a thickener, and using water as a dispersion medium. The ratio of the negative electrode active material, binder, and thickener was 97.4:2.0:0.6 by mass.
[0120] In each of the comparative examples in which pressing was performed, the negative electrode active material layer was pressed using a roll press machine so as to apply a pressure (linear pressure) of 40 kgf / mm or more.
[0121] For the negative electrodes of the obtained Examples and Comparative Examples, the graphite area ratio R excluding voids within particles, the average thickness of the negative electrode active material layer before charging and discharging, the density of the negative electrode active material layer, and the surface roughness ratio (R2 / R1) of the negative electrode base material were measured in the same manner as in Example 1. Table 1 shows the graphite area ratio R excluding voids within particles, the density of the negative electrode active material layer, the porosity of the negative electrode active material layer, and the surface roughness ratio (R2 / R1) of the negative electrodes of Examples 1 to 3 and Comparative Examples 1 to 6.
[0122] [evaluation] (Expansion of negative electrode active material during initial charging) Each of the obtained storage elements was charged once at a constant current constant voltage (CCCV) in a thermostatic chamber at 25°C under the conditions of a charging current (1 / 3C of the design (rated) capacity) and a charge cut-off voltage of 4.15V until the charging current became 0.01C or less, and the storage element was fully charged. In a glove box filled with argon with a dew point value of -60°C or less, the fully charged storage element was disassembled, and the negative electrode was washed with dimethyl carbonate (DMC). Using the washed negative electrode, the average thickness of the negative electrode active material layer at full charge was measured by the above-mentioned method. The amount of expansion of the negative electrode active material at the time of initial charge was calculated by subtracting the "thickness of the negative electrode active material layer before charging and discharging" from the "thickness of the negative electrode active material layer at full charge". The results are shown in Table 1.
[0123] (Capacity retention rate after storage) Each of the obtained storage elements was charged at a constant current and constant voltage (CCCV) in a thermostatic chamber at 25°C under the conditions of a charging current of 1 / 3C and a charge end voltage of 4.15V until the charging current was 0.01C or less, and then discharged at a constant current (CC) with a discharge current of 1C and a discharge end voltage of 2.75V, and the initial discharge capacity was measured. Next, in a thermostatic chamber at 25°C, the charging current was charged at a constant current and constant voltage (CCCV) with a charging current of 1 / 3C and a charge end voltage of 4.15V until the charging current was 0.01C or less, and the element was fully charged and left in an atmosphere at 60°C for 200 days. After leaving the element, constant current (CC) discharge was performed in an atmosphere at 25°C with a discharge current of 1C and a lower limit voltage of 2.75V, and the discharge capacity after leaving the element was measured. The discharge capacity after leaving the element relative to the initial discharge capacity was determined as the capacity retention rate after leaving the element. The results are shown in Table 1.
[0124] [Table 1]
[0125] As shown in Table 1, for example, when Example 2 is compared with Comparative Examples 1 to 3, it can be seen that the capacity retention rate after being left in a charged state is increased by using PVDF, a solvent-based binder, as the binder and not pressing the negative electrode active material layer. For example, Example 2, in which PVDF, a solvent-based binder, is used as the binder and the negative electrode active material layer is not pressed, was able to significantly increase the capacity retention rate after being left in a charged state compared to Comparative Example 2, in which PVDF, a solvent-based binder, is used as the binder and the negative electrode active material layer is pressed. On the other hand, Comparative Example 1, in which SBR, a water-based binder, is used as the binder and the negative electrode active material layer is not pressed, has a slightly higher capacity retention rate after being left in a charged state compared to Comparative Example 3, in which SBR, a water-based binder, is used as the binder and the negative electrode active material layer is not pressed, but the performance improvement effect is not as great as that of Example 2. A similar tendency can be seen from a comparison between Example 3 and Comparative Examples 4 to 6. From this, it was confirmed that the use of a solvent-based binder in combination with a non-pressed negative electrode active material layer achieves a higher capacity retention rate improvement effect after being left in a charged state than the use of a water-based binder in combination with a non-pressed negative electrode active material layer. In other words, it can be said that by using a solvent-based binder in combination with a non-pressed negative electrode active material layer, a storage element with a high capacity retention rate after being left in a charged state can be obtained as a synergistic effect of such a combination. Furthermore, when comparing Examples 1 to 3, it can be seen that Example 1, which uses solid graphite with a small average particle size as the negative electrode active material and has a small porosity of the negative electrode active material layer, has a higher capacity retention rate after being left in a charged state. In addition, it can be seen from each Example and Comparative Example that the expansion of the negative electrode during initial charging can be suppressed by not pressing the negative electrode active material layer. [Industrial Applicability]
[0126] The present invention is suitably used as an electricity storage element, including a non-aqueous electrolyte secondary battery used as a power source for electronic devices such as personal computers and communication terminals, automobiles, and the like. [Explanation of symbols]
[0127] 1 Energy storage element 2 Electrode body 3 Cases 4 Positive terminal 4' Positive electrode current collector 5 Negative terminal 5' Negative electrode current collector 6 Lid 8 Central part 20 Energy Storage Unit 30 Energy storage device
Claims
1. a negative electrode having a negative electrode substrate and a negative electrode active material layer laminated on the negative electrode substrate directly or via another layer; and a non-aqueous electrolyte; the negative electrode active material layer contains graphite and a solvent-based binder, The porosity of the negative electrode active material layer is 35% or less, an electric storage element in which the ratio of the surface roughness of the negative electrode base material in a region where the negative electrode active material layer is not laminated to the surface roughness of the negative electrode base material in a region where the negative electrode active material layer is laminated is 0.90 or more.
2. The energy storage element according to claim 1 , wherein the graphite comprises solid graphite.
3. 3. The energy storage element according to claim 1, wherein the graphite has an average particle size of 10 μm or less.
4. Laminating a negative electrode active material layer directly or via another layer on the negative electrode substrate; and Preparing the non-aqueous electrolyte Equipped with the negative electrode active material layer contains graphite and a solvent-based binder, The porosity of the negative electrode active material layer is 35% or less, The method for producing an electric storage element does not include pressing the negative electrode active material layer.
Citation Information
Patent Citations
Electrochemical device
JP2003151535A
Negative pole material for lithium battery, and lithium battery
JP2005222933A
Nonaqueous lithium secondary battery
JP2011040179A
Negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2012129170A
Negative electrode material for lithium ion secondary battery and production method therefor, negative electrode material for lithium ion secondary battery, and lithium ion secondary battery
JP2014035793A